Factors affecting hydraulic conductivity of asphalt mixture - Aboufoul, M.; Garcia, Alvaro (Springer Verlag, 2017)
In this paper, the topological properties of air voids in asphalt mixture: air void content, average void diameter, Euler number, genus, enclosed cavities, percolation number, aspect ratio, circularity and tortuosity were analysed using X-ray tomography scans and related to the hydraulic conductivity of a wide range of asphalt mixtures representative of those commonly used in practice. Moreover, a model for the hydraulic conductivity of asphalt mixture that is valid for the whole range of air void content was proposed. The model is based on statistical and physical considerations that lead to a system of functional equations. Finally, the model was related to experimental and literature data. It was observed that the range of asphalt mixtures studied hydraulic conductivity is related mostly to the air void content, while the topological parameters (e.g. tortuosity or aspect ratio) are not the primary factors affecting hydraulic conductivity. For this reason, the hydraulic conductivity of asphalt mixture commonly used in practice can be predicted using a simple hyperbolic equation with fixed, known, parameters.